Lazy Scheduling of Processing and Transmission Tasks in Collaborative Systems - Junuzovic, Sasa; Dewan, Prasun (GROUP 2009, 2009)
A collaborative system must perform both processing and transmission tasks. We present a policy for scheduling these tasks on a single core that is inspired by studies of human perception and the real-time systems field. It lazily delays the execution of the processing task if the delay cannot be noticed by humans. We use simulations and formal analysis to compare this policy with previous scheduling policies. We show that the policy trades-off an unnoticeable degradation in performance of some users for a much larger noticeable improvement in performance of others.